Graveyard shift : a novella - Rio, M. L. (Flatiron Books, 2024)
"The author of sales sensation If We Were Villains returns with a story about a ragtag group of night shift workers who meet in the local cemetery to unearth the secrets lurking in an open grave. Every night, in the college's ancient cemetery, five people cross paths as they work the late shift: a bartender, a rideshare driver, a hotel receptionist, the steward of the derelict church that looms over them, and the editor-in-chief of the college paper, always in search of a story. One dark October evening in the defunct churchyard, they find a hole that wasn't there before. A fresh, open grave where no grave should be. But who dug it, and for whom? Before they go their separate ways, the gravedigger returns. As they trail him through the night, they realize he may be the key to a string of strange happenings around town that have made headlines for the last few weeks-and that they may be closer to the mystery than they thought. Atmospheric and eerie, with the ensemble cast her fans love and a delightfully familiar academic backdrop, Graveyard Shift is a modern Gothic tale in If We Were Villains author M. L. Rio's inimitable style."--